Molecular determinants of response to PD-L1 blockade across tumor types - Romain Banchereau (Nature Portfolio, 2021)
PD-L1 immune checkpoint inhibition has been used for several tumour types. Here, the authors use immunohistochemistry, tumour mutation burden and RNA-seq data from 366 patients with different indications to identify molecular signatures of response to atezolizumab and reveal pathway heterogeneity and the involvement of non-immune pathways.